2020
DOI: 10.1186/s12889-020-08926-9
|View full text |Cite
|
Sign up to set email alerts
|

Use and importance of different information sources among patients with rare diseases and their relatives over time: a qualitative study

Abstract: Background: Finding reliable information on one of more than 7000 rare diseases is a major challenge for those affected. Since rare diseases are defined only by the prevalence criterion, a multitude of heterogeneous diseases are included. Common to all, however, are difficulties regarding information access. Even though various quantitative studies have analyzed the use of different information sources for specific rare diseases, little is known about the use of information sources for different rare diseases,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
10
0
5
Order By: Relevance
“…Most patients appreciated the PROMPT patient information sheet provided by healthcare providers on the first day of treatment, though some could not read and write. The latter should not ignore the value of supplement information material to patients because multiple information channels have reported improving understanding and knowledge of a particular subject matter [27]. Disclosing the phone number of a provider in the PROMPT patient information sheet aimed to facilitate patient-provider communication, mainly when a patient is far from the facility and needs immediate medical attention or advice.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients appreciated the PROMPT patient information sheet provided by healthcare providers on the first day of treatment, though some could not read and write. The latter should not ignore the value of supplement information material to patients because multiple information channels have reported improving understanding and knowledge of a particular subject matter [27]. Disclosing the phone number of a provider in the PROMPT patient information sheet aimed to facilitate patient-provider communication, mainly when a patient is far from the facility and needs immediate medical attention or advice.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient information is a common barrier in the context of rare diseases [ 19 ]. These limitations in quantity and quality of information can lead parents to scavenge multiple information sources, including peer support, internet searches, and social media [ 20 , 21 ]. Information barriers in rare diseases have also been linked to delays in diagnosis and misdiagnosis [ 18 , 22 ] Similarly, studies have demonstrated deficiencies in clinician knowledge about rare diseases and called for trustworthy, accessible information sources for clinicians [ 23 ] Parents of children with rare disorders frequently report knowing more about the disease than their clinicians, which can lead to complications in the clinical relationship and diminished trust [ 24 , 25 ] Our findings suggest that, in the context of complex VMs, parents' increased advocacy and information-seeking results in them knowing more about the disease and system of care.…”
Section: Discussionmentioning
confidence: 99%
“…For those affected, finding reliable information on rare diseases is a major challenge. Limited data is available regarding the use of information sources for various rare diseases, or how the usefulness of the information is evaluated by patients and their families (Litzkendorf et al, 2020 ). One qualitative study reported patients with various rare diseases and their close relatives considered the internet as the most important and widespread information source.…”
Section: Social Mediamentioning
confidence: 99%
“…Self-help associations and specialized clinicians help in filling the information gaps (Litzkendorf et al, 2020 ). Facebook is used commonly as a source of health-related information.…”
Section: Social Mediamentioning
confidence: 99%